Design and Implementation of the Line Follower Robot Based on Single Pole Double Through Relay by Using Microcontroller - Taj, A.B.; Ahmad, M. (The Nucleus, 2022)
The aim of this paper is to achieve the efficient control design for the line follower robot based on Single Pole Double Through (SPDT) relays by using PROTEUS professional software and its practical implementation. It followed a white line on the black background, detects turns or nonconformities, and operates the motors very efficiently by using the microcontroller. Infrared (IR) sensors are used to sense the white line (path). Differential directing was utilized to turn ON the robot. In this paper, we have the voltage from the comparator by using the IR sensors. Microcontroller AT89C51 reads the voltage from comparator and operates the relays and these relays further operate the Direct Current (DC) motors. Each rear wheel has a dedicated DC motor while the front wheel is free to rotate. The design and hardware implementation with microcontroller are presented in this paper. Multiple tests were carried out on the robot for the validation of ability to follow the white line by adopting the accurate path and successfully achieved the target. It is worth mentioning that the robot has successfully achieved the target by using the AT89C51 microcontroller.